Dataset of theoretical Molecular Electrostatic Potential (MEP), Highest Occupied Molecular Orbital-Lowest Unoccupied Molecular Orbital (HOMO-LUMO) band gap and experimental cole-cole plot of 4-(ortho-, meta- and para-fluorophenyl)thiosemicarbazide isomers - Sharmili Silvarajooa (Tanjong Malim, 2020)
Dataset of theoretical Molecular Electrostatic Potential (MEP), Highest Occupied Molecular Orbital-Lowest Unoccupied Molecular Orbital (HOMO-LUMO) band gap and experimental cole-cole plot of 4-(ortho-, meta- and para-fluorophenyl)thiosemicarbazide isomers by Sharmili Silvarajooa